(untitled) (Bangladesh Journal of Medical Science, 2026)
Objective This study examines the key drivers of motivation and their impact on job satisfaction among healthcare workers in a private hospital in Dhaka, Bangladesh, with implications for organizational performance. Methodology Using a cross-sectional survey, data were collected from 100 healthcare employees across different departments to assess their satisfaction levels with various financial (e.g., salary, bonuses, benefits) and non-financial (e.g., training, interpersonal relationships, promotion, and career advancement) motivators. Results The findings indicate that multiple elements contribute to job satisfaction, although their influence varies. While institutional benefits such as bonuses and medical facilities were associated with higher satisfaction, dissatisfaction with salary levels was prominent. Positive interpersonal relationships and supportive workplace culture emerged as vital contributors to employee motivation and overall job satisfaction. Conclusion The study highlights the importance of a holistic approach to workforce motivation in healthcare. Strategic attention to fair compensation, transparent promotion practices, and formal recognition mechanisms can enhance job satisfaction, reduce turnover, and improve service delivery in healthcare institutions. BJMS, Vol. 25 No. 01 January’26 Page : 290-296